A Rapid Test Kit for Dust Mite Allergen Detection: Enabling Patient Self-Testing and Environmental Control Assessment - He Zhang; Haibo Jiang; Jiarui Wan; Min Zhou; Guixian Liang; Fengwen Shan; Xinyi Zheng; Yana Zhang; Lei Cheng; Wu Yuan; Jing Su; Qilin Zhou; et al. (International Archives of Allergy and Immunology, 2026)
Background: House dust mites (HDM) are the most prevalent indoor allergens and a major contributor to allergic diseases worldwide. Effective monitoring of HDM allergen exposure is critical for clinical management and environmental control, yet the current gold-standard ELISA method is costly, complex, and unsuitable for self-testing. Objective: To develop and validate a rapid, semi-quantitative test kit for dust mite allergens that enables patient self-assessment and localized evaluation of environmental control measures. Methods: A total of 80 dust samples were collected from 59 homes of HDM-allergic patients in Guangzhou, China. Samples were analyzed using both ELISA and a novel colorimetric guanine-based rapid test. Allergen concentrations of Der 1 were quantified, and correlation, consistency, sensitivity, and specificity of the rapid test were assessed against ELISA results. Patients and researchers independently performed and interpreted the test to assess inter-rater reliability. Results: The rapid test strongly correlated with ELISA for total group I allergen concentrations (r = 0.83, P < 0.0001). All samples exceeding 10 μg/g were accurately identified (sensitivity = 100%, specificity = 79.1%). Classification agreement with ELISA was moderate (weighted κ = 0.557), and inter-rater agreement between patients and researchers was strong (weighted κ = 0.878). The test required only 20 mg of dust and delivered results within 5 minutes. Conclusion: The rapid test kit demonstrated high accuracy and reliability in identifying moderate- and high-level HDM allergen exposure. Its low cost, ease of use, and strong agreement with ELISA supports its utility in routine self-monitoring and localized environmental assessments, bridging a critical gap between clinical recommendations and real-world implementation.